Food intolerance in patients with functional abdominal pain: Evaluation through endoscopic confocal laser endomicroscopy - Gjini, Besmir; Melchior, Ilka; Euler, Philipp; Kreysel, Christian; Kalde, Sigrid; Krummen, Britta; Kiesslich, Ralf; Hemmerlein, Bernhard; Frieling, Thomas (Endoscopy International Open, 2023)
Background and study aims Gastrointestinal symptoms assumed to be caused by food intolerance are reported frequently in the general population. There is a significant difference between self-reported and objective proven food intolerance, as shown by placebo-controlled, double-blind, randomized trials. This discrepancy may be overcome by endoscopic confocal laser endomicroscopy (eCLE).Patients and methods In an observational study we evaluated 34 patients with functional abdominal pain and adverse reaction to food by eCLE and local duodenal food challenge for the first time. Spontaneous and food-induced transfer of fluorescein into the duodenal lumen was detected 10 minutes after intravenously application of fluorescein and 10 minutes after duodenal food challenge (DFC).Results Of the patients, 67.6 % responded with a fluorescein leakage into the duodenal lumen. Frequency rank order of food antigens that induced a response were soy (50 %), wheat (46.1 %), milk (20 %), egg (12 %), and yeast (11.5 %), respectively. Of the patients, 23.5 % showed spontaneous leakage of fluorescein, suggesting leaky gut syndrome. Histology of duodenal biopsies and mast cell function were normal. Overall, 69.5 % of patients improved with food exclusion therapy and 13 % were symptom-free according to eCLE. Conclusions The results of our study indicate that eCLE is a clinically useful tool to evaluate patients with functional abdominal pain and adverse reaction to food and to create individualized dietary therapy with clinical benefit for patients.